Implementasi Pemanfaatan Pembangkit Listrik Tenaga Surya (PLTS) untuk Peningkatan Produktivitas Budidaya Ikan dan Pertanian di Kalurahan Sumbersari - Muntini, Melania Suweni; Rahayu, Lucky Putri Putri; Fatimah, Iim; Faridawati, Faridawati; Suyatno, Suyatno; Yuwana, Lila; Indrawati, Susilo (Universitas Syiah Kuala, 2024)
Kalurahan Sumbersari, a border village in Sleman Regency, possesses significant potential in natural resources, particularly in agriculture and fisheries. However, the village faces substantial challenges, including inadequate aeration systems for fishponds and irrigation difficulties for rice fields. This community service initiative aims to address these issues by implementing solar energy-based solutions. The activities involved the design of an optimized aeration system for fishponds, the strategic installation of water pumps to facilitate rice field irrigation, and the construction of a Solar Power Plant (PLTS). The adoption of solar energy not only aims to meet the electricity needs but also contributes to Indonesia's achievement of the Sustainable Development Goals (SDGs), particularly Goal 7, which focuses on Affordable and Clean Energy. The success of this project hinged on the active participation of the local community. Socialization and training sessions were conducted to ensure understanding of the aeration systems, water pump operations, and PLTS maintenance. It is anticipated that the implementation of these activities will resolve the fish health issues and irrigation difficulties, thereby enhancing fish and agricultural production in Kalurahan Sumbersari. In addition to these direct benefits, the use of renewable energy is also expected to mitigate the negative environmental impacts associated with fossil fuel energy consumption.